Risk Assessment of Surplus Appropriation Schemes in Participating Life Insurance - Bohnert, Alexander; Gatzert, Nadine (Zeitschrift für die gesamte Versicherungswissenschaft, 2011)
The aim of this paper is to analyze a life insurance company's risk exposure with respect to different surplus appropriation schemes in participating life insurance. In this regard, three surplus appropriation schemes are considered, including the bonus system, the interest-bearing accumulation, and the system of shortening the contract term. We further examine an insurance company that offers all three schemes, i.e. each system is used for one third of the policyholders. Focus is laid on the effect of different asset portfolios and shocks to mortality on the insurer's risk situation with respect to the policyholder's age level at contract inception.
WiSo-Import:2015-03-26:2683